Linkedin, Quantitative Analysis to Examine Members#x2019; Behavior and Motivations (Global Journal of Management and Business Research, 2020)
Social media is one of the most popular Internet activities nowadays, and not surprisingly, it is at the core of business strategies. One cannot measure the popularity of a social media platform only by the size of its member base but, more importantly, by the number of active users. The higher the number of active users in a social media platform, the higher the potential for future growth and the opportunities to monetize their services. Social media platforms should, therefore, make every effort to encourage more users to be active.